Harassment and abuse of Indian women on dating apps: a narrative review of literature on technology-facilitated violence against women and dating app use - Benson Rajan (Humanities & Social Sciences Communications)
Abstract Dating app use can be precarious for Indian women, as they often face the risk of catfishing, stalking, harassment, abuse, and even physical violence. This narrative review synthesises the growing body of literature on Technology-Facilitated Violence Against Women (TFVAW), incorporating a specific focus on Indian women’s experiences with dating apps. While there is a growing body of research on TFVAW, the specific focus on Indian women’s experiences with dating apps remains underexplored. By building upon the broader research on TFVAW, this review aims to bridge the knowledge gap surrounding the experiences of Indian women in this context. The literature highlights several prominent types of harassment that women experience on online platforms in India. These include image-based abuse (IBA), cyberstalking, e-bile, doxing, and gender trolling. The narrative review shows that the abuse and harassment women face on dating apps have significant impacts on their mental health. Additionally, the existing dominant socio-cultural factors play an enabling role in facilitating harassment and abuse, leading some women to withdraw from dating platforms altogether.